PROFESSIONAL TA’LIM MUASSASALARI O‘QUVCHILARDA QURUVCHI KASBIGA OID KOMPETENSIYALARINI SHAKLLANTIRISHNING DIDAKTIK TA’MINOTINI TAKOMILLASHTIRISH - Eshmurod Murtazayev (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2020)
This article is devoted to the content, quantity and quality of education in new vocational education institutions, the reform of educational programs, technologies, factors that determine the quality and effectiveness of training, and their improvement